GAYA BAHASA PADA LAGU BATAK TOBA OLEH TRIO AMBISI DALAM ALBUM BERJUDUL 10 KARYA NAHUM SITUMORANG - Siboro, Martina Enjeli; Khairani, Ita (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This article aims to identify and describe the language style, meaning and cultural values of the Toba Batak contained in the Batak song by Trio Ambisi in the album entitled 10 Karya Nahum Situmorang. The data in this study are the lyrics of the Toba Batak song by Trio Ambisi in the album 10 by Nahum Situmorang. The instrument in this study is a human instrument, namely researchers who play an important role in research. This study used descriptive qualitative method. The results of the research found in the Toba Batak song by Trio Ambisi in his album entitled 10 by Nahum Situmorang are 10 figures of comparison, 10 figures of contrast, 3 styles of linkage and 15 figures of repetition. The meanings contained in the Toba Batak song by Trio Ambisi in his album entitled 10 by Nahum Situmorang are 5 connotative meanings, namely meanings that are not real or have experienced an expansion of meaning in terms of taste values and 5 songs have denotative meanings, namely plain meanings or true meanings. without adding to the flavor of the lyrics of the song. As for the cultural values contained in the Toba Batak song by Trio Ambisi in his album entitled 10 Karya Nahum Situmorang, there are 4 hagabeon values, 3 hamoraon values, 4 hamajuon values, 4 marsisarian values, 2 kinship values and 1 religious value. It is important for listeners of Batak songs to pay attention to the meaning of the song, the cultural values and style of language contained in the song in order to be able to understand the picture or essence of the story of the song.